Instantaneous deformability of high performance concretes with crushed aggregates - Góra, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
The test results presented concern high performance concretes of the w/c ratio 0,28. There have been examined the modulus of elasticity, Poisson’s ratio and limiting strain at the highest compressive stress. The variable factor in the studies is the type of coarse aggregate: crushed basalt, dolomite and granite. The results of the research have been tested statistically – the one-way ANOVA and the LSD test. There is stated the significant influence of aggregate on the tested deformation properties of high performance concretes.